Lithium ferrite (LiFe5O8)/polymethyl methacrylate (PMMA) nano-composite used in high dielectric constant capacitor and electromagnetic applications - Gamal M. Nasr; Emad Mousa; Mariam M. Haroun (Egyptian Journal of Petroleum)
Poly methyl methacrylate/ Lithium ferrite nano-composites have been prepared by solution mixing process. The electrical conductivity and dielectric properties of these prepared nano-composite have been investigated in the frequency range 102–106 Hz at different LiFe5O8 concentrations from 0 vol% to 25 vol%. The prepared samples are studied by thermal gravimetric analysis (TGA) and X-ray diffraction (XRD). Moreover, the magnetic properties of these nano-composites are investigated through vibrating sample magnetometer studies. XRD spectral investigation revealed that the structural of PMMA and its chemical characterization are appreciably affected by mixed lithium ferrite filler. The thermal stability of the PMMA matrix was found to increase appreciably by LiFe5O8 loading. The (I-V) characteristic of these nano-composites are in very good agreement with the non-linearity predicted by Kaiser et al. model. The effective dielectric constant is studied through different proposed models. Saturation magnetization of 10.05 emu/g is achieved for PMMA sample loaded with 25 vol% of LiFe5O8 particles. Keywords: PMMA, Dielectric constant, AC conductivity, Magnetization, Nano-composites, Li-Ferrite